2011
DOI: 10.14507/epaa.v19n33.2011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Performance Funding on Retention and Graduation Rates

Abstract: As the architect of the oldest and most stable performance funding program, Tennessee provides a unique opportunity to analyze the impact of changes in performance funding policies on changes in institutional retention and six-year graduation rates over time. Utilizing spline linear mixed models, this study examines the impact of changes in Tennessee’s performance funding policies on retention and six-year graduation rates at public four-year institutions from 1995-2009. The results show tying retention and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 24 publications
3
63
0
Order By: Relevance
“…In recent years, there have been several initiatives, at both the state and federal levels, to directly link performance to funding (Aldeman and Carey 2009a;Burke 2002;Zumeta 2001). While there have been a few attempts to uncover the impacts associated with these higher education performance funding policies (Volkwein and Tandberg 2008), our knowledge about them has thus far largely been based on anecdotal evidence and limited case studies (Banta, Rudolph, Dyke, and Fisher 1996;Doyle and Noland 2006;Sanford and Hunter 2010). As such, there remain serious gaps in our empirical knowledge about the extent to which these policies are having substantive impacts on budgetary processes at the state level and on service delivery at the organizational level.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been several initiatives, at both the state and federal levels, to directly link performance to funding (Aldeman and Carey 2009a;Burke 2002;Zumeta 2001). While there have been a few attempts to uncover the impacts associated with these higher education performance funding policies (Volkwein and Tandberg 2008), our knowledge about them has thus far largely been based on anecdotal evidence and limited case studies (Banta, Rudolph, Dyke, and Fisher 1996;Doyle and Noland 2006;Sanford and Hunter 2010). As such, there remain serious gaps in our empirical knowledge about the extent to which these policies are having substantive impacts on budgetary processes at the state level and on service delivery at the organizational level.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found that higher education leaders hold significant reservations regarding the appropriateness of various metrics used in performance funding policies (Dougherty & Reddy, 2013;O'Neal, 2007;Sanford & Hunter, 2011). Almost all participants in this study (both university administrators and state leaders) echoed those findings and discussed concerns with how the data should be measured and analyzed in the policy creation process.…”
Section: Data Concernsmentioning
confidence: 56%
“…First, to date, no study has examined Michigan's performance funding policy, whereas numerous studies have examined other common states such as Tennessee (Dougherty et al, 2014b;Dougherty & Natow, 2009;Hall, 2000;Lahr et al, 214;Sanford & Hunter, 2011), Ohio (Dougherty et al, 2014;Lahr et al, 214;O'Neal, 2007;Schaller, 2004), Florida (Bell, 2005;Dougherty & Natow, 2009) and Indiana (Dougherty et al, 2014;Lahr et al, 214;Umbricht, Fernandez, & Ortagus, 2015). Second, at the time of research, it was one of the most recent states to implement a performance funding policy.…”
Section: Case Study Contextmentioning
confidence: 99%
“…For most states the majority of funding comes from state allocations other than performance-based formulas. However, institutions have to divert resources from current needs toward compliance with state mandates for performance-based standards (Sanford & Hunter, 2011) with little to show in return (Sanford & Hunter, 2011;Shin, 2010;Volkwein & Tandberg, 2008). "[R]ecent studies have concluded that performance-funding-oriented reforms have had negligible impacts on organizational performance and student outcomes" (Rabovsky, 2014: p. 763).…”
Section: Journal Of Educational Issuesmentioning
confidence: 99%